Ab Initio Electronic Circular Dichroism of Fullerenes, Single‐Walled Carbon Nanotubes, and Ligand‐Protected Metal Nanoparticles. Issue 9 (8th July 2014) - Noguez, Cecilia; Hidalgo, Francisco
ABSTRACT The versatility and applicability of a time‐perturbed density functional method implemented within the SIESTA program package to calculate electronic circular dichroism of diverse nanoparticles is discussed. Results for nanostructures, such as fullerenes, single‐wall carbon nanotubes, as well as metallic nanoparticles composed of up to hundreds of atoms were examined by comparison with previously reported experimental and theoretical results. In all cases, the calculated electronic circular dichroism shows very good consistency with other calculations, and a remarkable agreement with experiments. It is concluded that such a high‐level method provides theoretical support for the quantification, understanding, and prediction of chirality and its measurement in nanostructures. It is expected that this information would be useful to motivate further experimental studies and interpretation of optical activity in terms of electronic circular dichroism in novel nanostructures. Chirality 26:193–202, 2014. © 2014 Wiley Periodicals, Inc.